2017
DOI: 10.21577/0103-5053.20170222
|View full text |Cite
|
Sign up to set email alerts
|

Structure/Activity of PtII/N,N-Disubstituted-N’-acylthiourea Complexes: Anti-Tumor and Anti-Mycobacterium tuberculosis Activities

Abstract: The syntheses, characterization, cytotoxicity against tumor cells and anti-Mycobacterium tuberculosis activity assays of Pt

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…According to the data from Table , the complex showed a moderate inhibitory action against mycobacterium tuberculosis (H37Rv ATCC 27294) when compared to the reference drug (ethambutol). Also, the observed MIC values suggest that the complex is active against the tumor cells MDA‐MB 231 (6.92 ± 0.60) and DU‐145 (3.09 ± 1.1), although lower than other platinum(II) and palladium(II) complexes previously obtained by us , , …”
Section: Resultsmentioning
confidence: 62%
“…According to the data from Table , the complex showed a moderate inhibitory action against mycobacterium tuberculosis (H37Rv ATCC 27294) when compared to the reference drug (ethambutol). Also, the observed MIC values suggest that the complex is active against the tumor cells MDA‐MB 231 (6.92 ± 0.60) and DU‐145 (3.09 ± 1.1), although lower than other platinum(II) and palladium(II) complexes previously obtained by us , , …”
Section: Resultsmentioning
confidence: 62%
“…A class of ligands that our research group has studied is acylthiourea. These are promising ligands due to their antibacterial, antiviral, and anticancer properties, , in addition to their structural versatility to be coordinated with metals by S, N, and O atoms, and they have a variety of binding modes to the metal center such as neutral monodentate (S), monobasic bidentate (O,S) or (N,S), and neutral bidentate (O,S). , Additionally, our research group reported a series of Ru­(II) compounds containing the acylthiourea ligands that exhibit cytotoxic activities and induce cell death by apoptosis in tumor cells. Pd­(II) and Pt­(II) complexes containing these ligands also showed relevant biological properties. …”
Section: Introductionmentioning
confidence: 99%